Design of rectangular microstrip patch antenna using stepped cut at four corners for broadband/ multiband application - Abdulrab, Waheeb Salim; Islam, Md Rafiqul; Habaebi, Mohamed Hadi (Asian Research Publishing Network (ARPN), 2015)
Design of rectangular microstrip patch antenna (RMPA) using stepped cut at four corners for broadband/multiband application is presented in this paper. Stepped cut at four corner technique is used in order to increase the bandwidth and gain of the antenna. Design and simulation of Modified rectangular microstrip patch antenna are done by CST Microwave Studio software. Four stages are presented for the proposed broadband MRMPA design. The first stage is a single mode RMPA and by increasing steps at the corner of the patch antenna a dual band, multiband and broadband are obtained. As the steps are increased, the antenna's operating bandwidth is also enhanced. The frequencies ranges of this design vary from 900MHZ to 3.5 GHz. Hence this design can be used for GSM (900MHz/1.5GHz), WiFi (2.4GHz), LTE (2.6GHz) and WiMax (3.5 GHz) applications.